Háztartási fogyasztói magatartás és jólét Magyarországon: Kísérlet egy modell adaptációjára - Zsombor Cseres-Gergely; György Molnár (Hungarian Academy of Sciences, Institute of Economics, 2008)
– The outcome of the economic performance of individuals is utilised in the form of consumption and consequent welfare. Despite this truism, there is relatively little information available on household consumption behaviour in Hungary stemming from investigations based on economic theory. The study sets out to fill the gap with an estimate based on the now-basic demand model. The authors apply the results of the estimate to verifying the robustness of the theoretical assumptions and then show how this framework can be used to quantify the effects of price changes and to calculate household consumption units. Within limits, the model proves applicable to the situation in Hungary. The results are comparable to those in international literature. The most instructive finding in practice is the one obtained from the examination of welfare; the model can correct significantly the results obtainable from a naive estimate of the effect of price changes that ignores adjustment by consumers. Additionally, it can be concluded from the consumption unit calculations that applying the widely used equivalence scales in Hungary may lead to over-estimation of the relative income position of families with children, especially those with several children.
Keywords: D12; 330; consumption theory; consumer behaviour; demand system; price index; consumption unit; Konsumentenverhalten; Konsumtheorie; Preisindex; Schätzung; Ungarn